2014
DOI: 10.1188/14.cjon.18-02ap
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Issues on the Impact of Smoking on Health-Related Quality of Life in Patients With Lung Cancer and Their Families

Abstract: Compelling evidence exists that continued smoking after a diagnosis of lung cancer adversely affects treatment effectiveness, survival, risk of recurrence, second malignancy, and health-related quality of life (HRQOL). The importance of HRQOL to patients with cancer and their families has been well documented. Because of increasing evidence of the benefits of smoking cessation, more research has focused on the impact of smoking on HRQOL. Smoking is a behavior that clusters in families; patients who smoke are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…Smoking cessation remains a tremendous challenge for some individuals with lung cancer (Cooley et al, 2009). Continued cigarette smoking and secondhand exposure complicate the recovery process and long-term QOL (McDonnell et al, 2014). Successful long-term smoking cessation is correlated with increased self-efficacy and improved symptom management, which may be achievable with behavioral intervention and pharmacotherapy (Cooley et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking cessation remains a tremendous challenge for some individuals with lung cancer (Cooley et al, 2009). Continued cigarette smoking and secondhand exposure complicate the recovery process and long-term QOL (McDonnell et al, 2014). Successful long-term smoking cessation is correlated with increased self-efficacy and improved symptom management, which may be achievable with behavioral intervention and pharmacotherapy (Cooley et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Eighty percent of individuals with a lung cancer diagnosis are former or current smokers (Park et al, 2012). For lung cancer survivors, continuing to smoke cigarettes negatively affects QOL, decreases lung capacity, increases the risk for comorbid diseases, and increases the mortality rate (Garces et al, 2004;McDonnell et al, 2014). Other unhealthy behaviors often accompany smoking, including lower physical activity levels, poor nutrition, and ineffective skills for self-management (Noble, Paul, Turon, & Oldmeadow, 2015).…”
mentioning
confidence: 99%
“…81,82 Support for tobacco cessation also can be viewed as an important part of the supportive care for patients who continue to smoke after a diagnosis of LC and their family members. 83 As described in the Surgeon General Report, interventions to help patients stop using tobacco are central to quality patient care. 78 For survivors, tobacco cessation is especially important as smoking is associated with a long list of diseases including chronic obstructive pulmonary disease and heart disease as well as second cancers that can also compromise quantity and quality of life.…”
Section: Tobacco Control Smoking Cessation and Supportive Carementioning
confidence: 99%
“…In general we can state that in our sample of patients, smoking appears to be a significant risk factor influencing QOL. The negative influence of smoking on quality of life for patients with lung cancer has been confirmed by other studies (Chen et al, 2012;Maliski et al, 2013;McDonnell et al, 2014). Although it has been indicated that patients who continue to smoke have poorer chances of survival than those who do not (Videtic et al, 2003;Chen et al, 2012).…”
Section: Discussionmentioning
confidence: 77%